Impact of the Use of Dikti Edu Tablets on Students’ Achievement in Computer Assisted Language Learning Class - Tagor Manurung; Melda Agnes Manuhutu; Lulu Jola Uktolseja; Sherly Gaspersz; Abraham Manuhutu (IJISTECH (International Journal of Information System and Technology), 2022)
The purpose of this research is to determine the impact of using the Dikti Edu Tablet on student achievement in the Computer Assisted Language Learning Class. Through this research, of course, researchers can find out the relationship between the independent variable, namely the use of Dikti Edu tablets, and the dependent variable, namely achievement. The research method is a quantitative research model using a survey in the form of distributing questionnaires to 20 students of the English Education Program. After collecting data, the data were analyzed quantitatively through SPSS 22 and the statements in the study used a Likert scale of 1-4. Based on the research that has been done, it is found that there is an increase in the learning achievement of English Education students at Victory Sorong University. This is evidenced by the value of the relationship between Edu Dikti Tablets and Student Achievement in English Language Education is 56%, while achievement is 44% which may be influenced by other factors not examined in this study. With the Edu Dikti Tablet, students are able to learn independently, creatively and innovatively so that they become educators who are ready to compete in the community